PAPILLOMA VIRAL INFECTION AMONG BOYS AND YOUNG MEN PRIMARY PREVENTION - M.G. Galitskaya; M.I. Ivardava (Union of pediatricians of Russia, 2009)
Young sexually active men may have anogenital HPV related infection, which can cause the genital penis verruca, penis cancer, perianal and anal cancer. Besides, men's HPV infection may cause an infection and subsequent diseases of cervix of the uterus and other organs among women. The available opportunity to inoculate boys and young men against HPV infection provides for 100% guaranteed protection from severe diseases not only for boys and young men but also for girls and women, who men may have sexual intercourse with.Key words: papilloma viral infection, men, prevention.